(untitled) (International Journal of Environmental Sciences, 2025)
The catering industry is undergoing a remarkable transformation driven by digital advancements and evolving consumer behaviors, with increasing reliance on digital platforms for restaurant discovery and interaction. The objective of this study is to evaluate the impact of digital marketing techniques and customer digital behavior on customer satisfaction and loyalty in the Chinese catering industry. The study employs the Technology Acceptance Model (TCM) as its theoretical base and uses a structured questionnaire to collect data from 280 catering enterprises in Beijing,Shanghai, Guangxi and Guangdong. The research findings are 1) Digital marketing adoption is widespread in the Chinese catering industry, with 85% using digital marketing and 91.07% maintaining a social media presence. 2) Effective digital marketing strategies (β = 0.25, p < 0.001) and understanding customer digital behavior (β = 0.22, p < 0.001) significantly enhance customer satisfaction, which in turn strongly drives customer loyalty (β = 0.60, p < 0.001). 3) Direct effects digital marketing and customer behavior to loyalty were also significant (β=0.25, p<0.001 and β=0.20, p<0.05). 4) Customer satisfaction plays a mediating role, with indirect effects from Digital Marketing Techniques and Customer Digital Behavior on loyalty. These results emphasize the importance of a comprehensive, strategic approach to digital marketing in the catering sector.